Differentiated approach to employee motivation in terms of finance - Hitka, Miloš; Lorincová, Silvia; Potkány, Marek; Balážová, Žaneta; Caha, Zdeněk (Journal of Business Economics and Management, 2021)
Motivating the employees is considered one of the essential manager’s skills. Knowledge of powerful motivation factors allow managers to motivate employees effectively. It results in motivated employees able to affect a success of enterprises and its competitive advantage. Following the research carried out using 34,000 Slovak employees, the importance of motivation factors relating to finance was defined. Tukey’s HSD test, as a part of the ANOVA analysis, was used for extensive investigation into the most important motivation factors relating to finance. It is supposed that motivation of employees of different gender, age and job position will differ. The suppositions were confirmed by the results achieved in the research showing significant differences between individual employee categories of managers, blue-collar workers and white-collar workers. Taking into consideration the results, managers are suggested to concentrate on motivating the employees as parts and not as a whole because of the differences in the needs of employees in terms of gender, age and mainly job position. First published online 30 October 2020